1-x-1-x-dx- Tinku Tara June 3, 2023 Integration 0 Comments FacebookTweetPin Question Number 492 by 123456 last updated on 25/Jan/15 ∫1−x1+xdx Answered by prakash jain last updated on 14/Jan/15 x=t2dx=2tdt∫1−t1+t⋅2tdt=2∫t−t21+tdt=2∫1+t+1−t2−21+t=2[∫1dt+∫(1−t)dt−∫21+tdt]=2[t+t−t22−2ln∣1+t∣]+C=4t−t2−4ln∣1+t∣+C=4x−x−4ln∣1+x∣+C Terms of Service Privacy Policy Contact: info@tinkutara.com FacebookTweetPin Post navigation Previous Previous post: 1-1-2x-dx-Next Next post: sec-3-xdx- Leave a Reply Cancel replyYour email address will not be published. Required fields are marked *Comment * Name * Save my name, email, and website in this browser for the next time I comment.